Maya and the return of the godlings - Barron, Rena (Barron, Rena. Maya and the Rising Dark., 2021)
Twelve-year-old Maya knows the Dark is still a threat, even though she crossed the veil and saved her dad from the Lord of Shadows. Now training as a guardian, Maya spends her time helping Papa repair the veil between their world and the Dark wherever tears appear, but something is wrong--her godling powers are not as strong as they should be. She and her friends learn a terrible truth then, which prompts them to return to the Dark to find a powerful weapon to stop the Lord of Shadows from making war on the human world.